Stimulation of Wild-Type, F508del- and G551D-CFTR Chloride Channels by Non-Toxic Modified pyrrolo[2,3-b]pyrazine Derivatives - Dannhoffer, Luc; Billet, Arnaud; Jollivet, Mathilde; Melin-Heschel, Patricia; Faveau, Christelle; Becq, Frederic (Frontiers in Pharmacology, 2011)
Cystic Fibrosis is a major inherited disorder involving abnormalities of fluid and electrolyte transport in a number of different organs due to abnormal function of Cystic Fibrosis Transmembrane conductance Regulator (CFTR) protein. We recently identified a family of CFTR activators, which contains the hit: RP107 [7-n-butyl-6-(4-hydroxyphenyl)[5H]-pyrrolo[2,3-b]pyrazine]. Here, we further evaluated the effect of the chemical modifications of the RP107-OH radical on CFTR activation. The replacement of the OH radical by a fluorine atom at position 2 (RP193) or 4 (RP185) significantly decreased the toxicity of the compounds without altering the ability to activate CFTR, especially for RP193. The non-toxic compound RP193 has no effect on cAMP production but stimulates the channel activity of wild-type CFTR in stably transfected CHO cells, in human bronchial epithelial NuLi-1 cells and in primary culture of human bronchial epithelial cells. Whole cell and single patch clamp recordings showed that RP193 induced a linear, time and voltage-independent current, which was fully inhibited by two different and selective CFTR inhibitors (CFTRinh-172 and GPinh-5a). Moreover, RP193 stimulates CFTR in temperature-rescued CuFi-1 (F508del/F508del) human bronchial epithelial cells and in CHO cells stably expressing G551D-CFTR. This study shows that it is feasible to reduce cytotoxicity of chemical compounds without affecting their potency to activate CFTR and to rescue the class 2 F508del-CFTR and class 3 G551D-CFTR CF mutant activities.